Adaptation of the medical ethics teaching questionnaire for the use of Taiwanese medical students: A developmental study / Lee Jing Ning - Lee, Jing Ning (2021)
Medical ethics is among one of the most important competencies in medical education and formal physicians' training. In the past decades, medical ethics education has become a priority within medical education institutions worldwide. In Taiwan, medical ethics was included in the undergraduate medical curricula since 1995. However, studentsï¿½ view upon graduation revealed that they were still lacked confidence about beginning their residency program due to limited understanding of ethical values. Taiwan, as a country with unique cultural belief in the traditional Confucian principles that emphasizes the virtue of ï¿½filial pietyï¿½ and family cohesion in medical decision-making is lacking Taiwanese studies that can represent studentsï¿½ view on current undergraduate ethics education. However, most of the existing survey instruments found in previous literature were written in English language. As for Taiwan that had showed "low proficiency" in the English First's (EF's) global English Proficiency Index (EPI), the high English proficiency level required to complete these survey instrument may cause reading difficulties among Taiwanese students. The research objectives of this study were to translate and adapt the Traditional Chinese version of a validated medical ethics education questionnaire for the use of medical students in Taiwan. The Tahra et al.ï¿½s (2017) questionnaire was selected due to its comprehensiveness in exploring studentsï¿½ preferences toward medical ethics education. The questionnaire with a total of 69 items was translated according to a simplified version of the Functional Assessment of Chronic Illness in Therapy (FACIT) translation methodology, including forward and back translation, comparing the back translation to source, expert reviewing, and cognitive debriefing. iv The translations were carefully revised when they revealed difficulty in understanding or showed high possibilities of causing misunderstanding. We also identified numerous challenges at the stage of expert reviews, including influence of idiomatic phrases, wording mistakes, subtle semantic difference of possible translations, morphology of language, and the ambiguity of translated Items. At the stage of cognitive interviews, respondents reflected that further interpretation is needed to better understand some of the questions, while some questions were asked to be deleted due to repetition or irrationality. This study completed the first translation of an authoritative English version of medical ethics teaching questionnaire to its Traditional Chinese version following a multiple steps translation methodology to ensure that the translated items are conceptually equivalent to its English source and are culturally adapted to the Taiwanese environment. The availability of this translation version will increase related research among the Taiwanese healthcare educators. Future work including psychometric testing on the translated questionnaire among the general population of Taiwan was suggested to create a final version of the survey instrument.